Technique and Man : Examining Jacques Ellul’s Concept of Technique and its Implications - Stucki, Max (fi=Turun yliopisto|en=University of Turku|, 2018)
The subject of this thesis is Jacques Ellul’s concept of technique. The effects of technique, as defined by Ellul, on society, state and human nature, are scrutinized. The aim is to follow Ellul’s thought to its logical conclusion and thus reveal the essence and implications of his concept of technique. The thesis is theoretical by nature and is based both on Ellul’s writings and the commentaries on his works. The single most important source material is Ellul’s book “The Technological Society”. Also, other sources related to the philosophy of technique are utilized. The central conclusion of the thesis is, that from Ellul’s concept of technique it seems to follow, that technique must be perceived as a kind of modern idol. The union of technique and human being on both material and spiritual level is the aim of technological development, and thus technique has, following Ellul’s thinking, dimensions, which cannot be taken to be purely material. The study of technique from a broad philosophical standpoint would benefit from further development of Ellul’s ideas. Based on the conclusions, further study on the subject of merging of technique and spiritual dimensions would be desirable, especially, to which extent the technological development and meanings attached to it can be seen as expressions of spirituality as well as political-ideological worldview.